Using Artificial Intelligence (AI) in Financial Decision-Making in the Agricultural and Rural Economy - Liliana Anghel (Journal of Agriculture and Rural Development Studies)
Using the artificial intelligence (AI) in financial decision-making in the agricultural and rural economy represents a significant innovation that can transform the way financial resources and strategies are managed in this sector. Agriculture and the rural economy usually face a variety of financial challenges, such as price volatility, unpredictable weather conditions, market risks and limited access to capital. In this context, AI can address many of these challenges and improve their economic efficiency and sustainability. The article explores a comparative analysis of the use of AI as an alternative to traditional methods considering important activities in the Agrico field as well as the interdependence between the optimization of the decision-making process in agriculture and the rural economy and regional development.